Analisis Pola Komunikasi Grup Indonesia Traveler pada Media Sosial Clubhouse - Khofifah, Nadira Shifa; Devi, Sofia Primalisanti (Prologia, 2023)
Indonesia Traveler Group is virtual communities contained in the Clubhouse application. Clubhouse is an audio-chat-based application that can be used to listen to and interact with other users in a discussion room. The purpose of the establishment of this Indonesia Traveler group is to make the Indonesia Traveler group as the main medium of exchanging ideas and sharing experiences with tourism players and all tourism stakeholders in Indonesia. This research aims to analyze communication patterns formed in the Clubhouse Indonesia Traveler group. By using a constructivist paradigm with a descriptive qualitative approach and analysis unit studied which are an active member in the Indonesia Traveler group. For data collection techniques using documentation, interviews and research observations. Checking the validity of the data in this study uses a test of source triangulation and data between the results of interview data and the interview data that has been conducted. Based on the results of the study, the communication pattern formed in the Clubhouse Indonesia Traveler group is Y pattern due to the presence of someone who becomes an intermediary to convey information with other members and also the pattern of all channels where the group discussion room is open so that members can communicate with each other. Grup Indonesia Traveler merupakan salah satu komunitas virtual yang terdapat dalam aplikasi Clubhouse. Clubhouse adalah aplikasi berbasis audio-chat yang dapat digunakan untuk mendengarkan sekaligus berinteraksi dengan pengguna lain dalamsebuah ruang diskusi. Pembentukan grup Indonesia Traveler ini adalah untuk menjadikan grup ini sebagai medium utama bertukar gagasan dan saling berbagi pengalaman dengan para pelaku pariwisata dan seluruh stakeholder pariwisata di Indonesia. Penelitianini bertujuan untuk menganalisis pola komunikasi yang terbentuk pada grup Clubhouse Indonesia Traveler. Penelitian inimenggunakan paradigma konstruktivis dengan pendekatan kualitatif deskriptif. Unit analisis yang diteliti adalah member aktifdalam grup Indonesia Traveler, menggunakan teknik pengumpulan data dokumentasi, wawancara dan observasi penelitian.Pengecekan keabsahan data pada penelitian ini menggunakan uji triangulasi antara sumber dan data hasil data wawancara serta observasi pada interaksi dalam grup. Hasil penelitian ini memperlihatkan pola komunikasi yang terbentuk dalam grup ClubhouseIndonesia Traveler adalah pola Y, dikarenakan kehadiran perantara untuk menyampaikan informasi dengan anggota lain, dan pola semua saluran pada ruang diskusi grup memperlihatkan keterbukaan dari bebasnya anggota berkomunikasi antara satu sama lain.